Practical transformer handbook - Gottlieb, Irving M.
This book shows how a transformer can be put to use, common problems which a user will face, and which is the most appropriate in a particular situation. Anyone working with transformers will find this a valuable user guide. Theory and mathematics are kept to a minimum, and instead the everyday working of these devices is described. Practical Transformer Handbook covers transformers in electronic technology, control techniques, instrumentation, and other more unusual applications. In this practical book a wide range of devices, uses and problems are explored, from parametric transformers, tran.